1998
DOI: 10.1021/jm981005y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monoamine Oxidase-B by Condensed Pyridazines and Pyrimidines:  Effects of Lipophilicity and Structure−Activity Relationships

Abstract: A number of condensed pyridazines and pyrimidines were synthesized and tested for their monoamine oxidase-A (MAO-A) and MAO-B inhibitory activity. Their lipophilicity was examined by measuring partition coefficients and RP-HPLC capacity factors, revealing some peculiar electronic and conformational effects. Further insights were obtained by X-ray crystallography and a thermodynamic study of RP-HPLC retention. Structure-activity relations highlighted the main factors determining both selectivity and inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 40 publications
2
63
1
1
Order By: Relevance
“…On the other hand, it has been previously shown that electrostatic interactions and charge-transfer bonding are important parameters in the interaction between inhibitors and the FAD cofactor of the MAO-A [77,78]. The results described by Altomare et al [74] revealed that the majority of the condensed pyridazines were selective towards MAO-B whereas the condensed pyrimidines were more active against MAO-A enzyme.…”
Section: D Qsar Using Multiple Linear Regression (Mlr)mentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, it has been previously shown that electrostatic interactions and charge-transfer bonding are important parameters in the interaction between inhibitors and the FAD cofactor of the MAO-A [77,78]. The results described by Altomare et al [74] revealed that the majority of the condensed pyridazines were selective towards MAO-B whereas the condensed pyrimidines were more active against MAO-A enzyme.…”
Section: D Qsar Using Multiple Linear Regression (Mlr)mentioning
confidence: 97%
“…Pyridazine and pyrimidine derivatives-Lipophilicity effects were investigated by Altomare et al [74] in a set of pyridazine and pyrimidine derivatives by measuring partition coefficients, thermodynamic and physicochemical parameters of RP-HPLC retention. The best equation extracted through MLR for a set of 14 pyridazine derivatives (see Fig3, structure 3) yielded an r 2 =0.821 and q 2 =0.704 (cross-validation) showing the importance of lipophilic, electronic and steric properties in the explanation of MAO-B inhibition.…”
Section: D Qsar Using Multiple Linear Regression (Mlr)mentioning
confidence: 99%
“…31 Alguns outros fatores estruturais são igualmente importantes no desenvolvimento de IMAO e devem ser considerados no desenho destas moléculas: i) lipofilicidade do inibidor, a qual é fundamental para atravessar a barreira hematoencefálica e, assim, inibir a enzima no cérebro; ii) a presença de ligações de hidrogênio entre grupos polares do inibidor e a enzima, principalmente envolvendo o grupamento flavina do cofator FAD ou os resíduos Tyr, Gln, Asn ou Glu presentes no sítio catalítico, estabilizando o complexo inibidor-enzima; iii) a presença de uma estrutura planar do inibidor, que possa melhor se adaptar à fenda catalítica. 32 Diversos estudos têm buscado isolar e caracterizar IMAO presentes em plantas. Um destes compostos é a 2,3,6-trimetil-1,4--naftoquinona (TMN, Figura 2), um inibidor reversível e competitivo de MAO isolado de folhas de tabaco.…”
Section: Figura 2 Estruturas De Alguns Inibidores De Mao Selegilinaunclassified
“…3-Arylpyrimido [4,5-c]pyridazine-5,7(6H,8H)-diones possess monoamine oxidase (MAO) inhibitory activity and substituents on the diazine nucleus modulate the inhibitory activity. 17 Monoamine oxidase (MAO) is an iron containing flavoenzyme that occurs within cells, bound to the surface membrane of mitochondria and involved in the degradation of biogenic amines. Monoamine oxidase inhibitors are the most important drugs for the clinical management of depression and Alzheimer disease.…”
Section: Introductionmentioning
confidence: 99%